Fernando Távora’s Japan through books : a fascination with tradition in search of innovation - Duarte, João Miguel Couto, 1966- (2021)
Amongst the private library of the Porto architect Fernando Távora (1923-2005), who is an obligatory figure if one wants to understand Portuguese architecture in the latter half of the 20th century, are several books on Japan and its architecture. Taken together, the books reveal a sustained interest in this subject matter, an interest which had begun when Távora was still a student of architecture and for which his visit to Japan in 1960 was to be decisive for its consolidation and deepening. In an initial phase, he became interested in contemporary Japanese architecture and the Western architecture that absorbed it, but traditional Japanese architecture was to become a more permanent object of interest for him. Here one can identify a fascination with tradition, whereby tradition is understood, in a broader sense, as permanence – of values and architectural practices. However, there is also undeniably a search for innovation, whereby innovation is understood in an equally full sense, as the creation of the new, a new way of architecture dealing with modernity. Proceeding from Japan and its architecture as revealed in his books, a completely new approach, this chapter sets out to discuss the extent of Távora’s fascination with tradition as a reflection of his search for innovation.